2019
DOI: 10.1080/10344233.2019.1672951
|View full text |Cite|
|
Sign up to set email alerts
|

Characterisation and deterioration of mineral papers

Abstract: Characterisation and deterioration of mineral papersMineral paper, also known as rich mineral paper, is a paper-like material manufactured from calcium carbonate with a small amount of high-density polyethylene (HDPE), instead of traditional cellulose-based fibres. For environmental reasons, mineral paper was designed to degrade when exposed to sunlight. It was the aim of this study to address the research gap in conservation literature describing the properties and degradation patterns of mineral paper.Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In other words, as the HDPE content in the mineral paper composition increased, the color change (darkening) also increased due to weathering or biological degradation. Similar to Chu and Nel's research, 19 it can be concluded that UV radiation greatly affects the mineral papers' color.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…In other words, as the HDPE content in the mineral paper composition increased, the color change (darkening) also increased due to weathering or biological degradation. Similar to Chu and Nel's research, 19 it can be concluded that UV radiation greatly affects the mineral papers' color.…”
Section: Resultssupporting
confidence: 74%
“…Although mineral paper appears similar to traditional paper, it technically is not actual paper because it lacks cellulosic fibers 18 . Furthermore, calcium carbonate is the primary ingredient in mineral paper, rather than an additive used as filler for a synthetic polymer base or cellulose paper 19 . The increasing awareness of the properties and usefulness of mineral papers, which do not contain toxic additives, has led to their widespread use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper being printable, recyclable and water proof is a plastic alternative with good credentials. Stone papers can be used to make certified food-grade packaging, greaseproof paper wraps, ziplock bags etc (Ezcurra et al, 2012;Chu et al, 2019;Indriati et al, 2020).…”
Section: Plastic Alternativesmentioning
confidence: 99%
“…The manufacturing process produces less effluent and consumes half as much energy as traditional paper-making. It may be recycled with plastics or remade into rich mineral paper again, and is not biodegradable but is photo-degradable under suitable conditions [7].…”
Section: Introductionmentioning
confidence: 99%